Cerebral arterio-venous malformations at Edgardo Rebagliati Martins Nacional Hospital - Rabanal, Jorge (1995)
A review of 50 cases with cerebral arterio.venous malformations (AVM) treated since Junly 1988 through December 1992 in the Neurosurgery Service from Edgardo Rebagliati Martins National Hospital was done. Clinical records, surgical techniques and pre- and post-operative studies were evaluted by retrospective analysis. The more important results were the frecuency of presentations in male patients from the coast, the clinical onset with intracraneal hemorrhage, the operative technique of drainage in the emergency and the mortality (15%). Clinical presentation, frequent localization at the parietal center, the management of AVM in pregnant woman were discussed in a comparative way. The Spetsler and Martin's gradation for AVM, the therapeutic counsel for each case and post-operative course ask for better implementation in the Neuro-surgery Service from Edgardo Rebagliati Martins National Hospital in order to improve the deficiencies found in the treatment of AVM.